Protective effect of the novel calcineurin inhibitor voclosporin in experimental colitis - Lindemann, Aylin; Roth, Dominik; Koop, Kristina; Neufert, Clemens; Zundler, Sebastian; Atreya, Raja; Neurath, Markus F.; Leppkes, Moritz (Frontiers in Medicine, 2023)
Background and aims Acute severe steroid-refractory ulcerative colitis remains a medically challenging condition with frequent need of surgery. It can be treated with the calcineurin inhibitor cyclosporine A with the need for therapeutic drug monitoring and significant toxicity. Recently, a novel calcineurin inhibitor, voclosporin, has been approved for the treatment of lupus nephritis with no need for therapeutic drug monitoring and an improved long-term safety profile. However, the therapeutic effect of voclosporin in acute severe steroid-refractory ulcerative colitis is still uncertain. We aimed to assess the therapeutic potential of voclosporin to ameliorate inflammation in an experimental model of colitis. Methods We used the dextran sodium sulfate-induced model of colitis in C57BL/6 J wildtype mice treated with either cyclosporine A, voclosporin or solvent control. We employed endoscopy, histochemistry, immunofluorescence, bead-based multiplex immunoassays and flow cytometry to study the therapeutic effect of calcineurin inhibitors in a preventive setting. Results Acute colitis was induced by dextran sodium sulfate characterized by weight loss, diarrhea, mucosal erosions and rectal bleeding. Both cyclosporine A and voclosporin strongly ameliorated the course of disease and reduced colitis severity in a similar manner. Conclusion Voclosporin was identified as biologically effective in a preclinical model of colitis and may be a potential therapeutic option in treating acute severe steroid-refractory ulcerative colitis.